Evaluation Of The Implementation Of The Independent Curriculum - Sularno Sularno (Green Publisher Indonesia, 2025)
The implementation of the Independent Curriculum in driving schools is a strategic step by the Ministry of Education and Culture in facing the challenges of the 21st century, which emphasizes competency-based learning, differentiation, and character. In this context, the subjects of Physical Education, Sports, However, the implementation of this new curriculum often faces obstacles, such as a lack of teacher understanding of the essence of the curriculum, limited facilities and infrastructure, and less than optimal collaboration between schools. This study aims to evaluate the implementation of the Independent Curriculum, especially in the subject of PJOK in Senior High Schools that are driving schools in Nunukan Regency. This study is an evaluative study using the CIPP (Context, Input, Process, Product) model approach developed by Stufflebeam. Data collection techniques in this study used observation, interview, questionnaire and documentation methods. In this study, the data analysis used was quantitative data analysis and qualitative data analysis. The results of the study showed that the implementation of the Independent Curriculum in the PJOK subject in the Driving Schools of the Senior High School level in Nunukan Regency has gone very well. This program is supported by conducive school policies and environments, adequate human resources and facilities, participatory and student-centered learning processes, and learning outcomes that demonstrate holistic competency achievements in accordance with the Pancasila student profile.